Fluvastatin Reduces Glucose Tolerance in Healthy Young Individuals Independently of Cold Induced BAT Activity - Felder, Martina; Maushart, Claudia Irene; Gashi, Gani; Senn, Jaël Rut; Becker, Anton S.; Müller, Julian; Balaz, Miroslav; Wolfrum, Christian; Burger, Irene A.; Betz, Matthias Johannes (Frontiers in Endocrinology, 2021)
Background Statins are commonly prescribed for primary and secondary prevention of atherosclerotic disease. They reduce cholesterol biosynthesis by inhibiting hydroxymethylglutaryl-coenzym A-reductase (HMG-CoA-reductase) and therefore mevalonate synthesis. Several studies reported a small, but significant increase in the diagnosis of diabetes mellitus with statin treatment. The molecular mechanisms behind this adverse effect are not yet fully understood. Brown adipose tissue (BAT), which plays a role in thermogenesis, has been associated with a reduced risk of insulin resistance. Statins inhibit adipose tissue browning and have been negatively linked to the presence of BAT in humans. We therefore speculated that inhibition of BAT by statins contributes to increased insulin resistance in humans. Methods A prospective study was conducted in 17 young, healthy men. After screening whether significant cold-induced thermogenesis (CIT) was present, participants underwent glucose tolerance testing (oGTT) and assessment of BAT activity by FDG-PET/MRI after cold-exposure and treatment with a β3-agonist. Fluvastatin 2x40mg per day was then administered for two weeks and oGTT and FDG-PET/MRI were repeated. Results Two weeks of fluvastatin treatment led to a significant increase in glucose area under the curve (AUC) during oGTT (p=0.02), reduction in total cholesterol and LDL cholesterol (both p<0.0001). Insulin AUC (p=0.26), resting energy expenditure (REE) (p=0.44) and diet induced thermogenesis (DIT) (p=0.27) did not change significantly. The Matsuda index, as an indicator of insulin sensitivity, was lower after fluvastatin intake, but the difference was not statistically significant (p=0.09). As parameters of BAT activity, mean standard uptake value (SUVmean) (p=0.12), volume (p=0.49) and total glycolysis (p=0.74) did not change significantly during the intervention. Matsuda index, was inversely related to SUVmean and the respiratory exchange ratio (RER) (both R2=0.44, p=0.005) at baseline, but not after administration of fluvastatin (R2=0.08, p=0.29, and R2=0.14, p=0.16, respectively). Conclusions Treatment with fluvastatin for two weeks reduced serum lipid levels but increased glucose AUC in young, healthy men, indicating reduced glucose tolerance. This was not associated with changes in cold-induced BAT activity.